Impact of COVID-19 on the Diagnosis and Surgical Treatment of Colorectal Cancer: A National Perspective. Issue 11 (9th August 2021) - Donlon, Noel E.; Hayes, Conall; Davern, Maria; Bolger, Jarlath C.; Irwin, Shane C.; Butt, Waqas T.; McNamara, Deborah A.; Mealy, Kenneth
Abstract : Supplemental Digital Content is available in the text.